THE EFFECT OF ACROSTIC TECHNIQUES ON INCREASING THE MASTERY OF GERMAN PREPOSITIONS ON STUDENTS OF GERMAN LANGUAGE EDUCATION STUDY PROGRAM - Carolina Lestuny; Kunu Hanna Grietje (EDU SCIENCES JOURNAL, 2021)
This study aimed to examine the effect of acrostic techniques on increasing student mastery of Präpositionen, which was conducted from September to November 2020. This research was an experimental study with research subjects being college students of the German language study program in the third semester of the academic year 2020/2021. The instruments used in data collection in this study were Pre-test, and Post-test questions before and after the acrostatic technique were applied in the learning process with German prepositions. The results showed that the acrostic technique significantly affected the increasing mastery of Präpositionen college students (thit= 7.67>ttab=1.77. Therefore, Acrostic techniques are recommended for use in präpositionen learning